2002
DOI: 10.1046/j.1365-2958.2002.03143.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation of a p44 pseudogene in Anaplasma phagocytophila by bacterial RNA splicing: a novel mechanism for post‐transcriptional regulation of a multigene family encoding immunodominant major outer membrane proteins

Abstract: SummaryImmunodominant 44 kDa major outer membrane proteins of Anaplasma phagocytophila (human granulocytic ehrlichiosis agent) are encoded by the p44 multigene family. One of the paralogues, p44-18 is predominantly expressed by A. phagocytophila in mammalian hosts, but is downregulated in the arthropod vector. The expression of p44-18 was upregulated in A. phagocytophila cultivated in HL-60 cells at 37∞ ∞ ∞ ∞ C compared with 24∞ ∞ ∞ ∞ C. However, the molecular mechanism of such gene expression was unclear, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 36 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…We did find one 'similarity group' that comprised paralogues from ruminant UK and human USA isolates, which was the 'p44-18 group'. It has been hypothesized that the p44-18 paralogue may have a somewhat specific role in the initial phase of infection of previously naïve animals and humans (Zhi et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did find one 'similarity group' that comprised paralogues from ruminant UK and human USA isolates, which was the 'p44-18 group'. It has been hypothesized that the p44-18 paralogue may have a somewhat specific role in the initial phase of infection of previously naïve animals and humans (Zhi et al, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids containing appropriately sized inserts (400-600 bp) were identified using standard protocols, purified (Wizard Plus SV Miniprep DNA Purification System; Promega) and their inserts were sequenced using primers T4 and SP7. The DNA sequences obtained were aligned in GCG with all (65 in number) of the available, published p44 paralogue gene sequences of A. phagocytophilum (Caspersen et al, 2002;Lin et al, 2002;Zhi et al, 1999Zhi et al, , 2002b, including those of the Webster and BDS 'strains', and the NY31, NY36, NY37, HZ and LL isolates from the USA (GenBank accession nos AF443396 to AF443413 and AF443415 to AF443419, AF059181, AF135263, AF135254 to AF135257, AF412818 to AF412831, AF414591 and AY064513 to AY064530).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on our results, it is unlikely that AacdtIVS-1 and AacdtIVS-2 belong to group I or II introns. Recently, the p44-1 IVS of Anaplasma phagocytophilum (the causative agent of the tick-borne disease human granulocytic ehrlichiosis) was reported to self-splice in vitro but to be structurally and mechanistically dissimilar to group I and II introns (45). Based on these findings, the authors suggested that p44-1 IVS could belong to a new group of bacterial introns.…”
Section: Resultsmentioning
confidence: 99%
“…Intervening sequences found in the tcdA and recA genes of C. difficile and B. anthracis, respectively, are removed from their precursor mRNAs, giving rise to proteins that are functionally indistinguishable from their intronless counterparts (2,15). More recently, bacterial RNA splicing was shown to function in a temperature-dependent fashion, as a novel means of regulating the expression of the major outer membrane protein gene (p44-18) of A. phagocytophilum (45). In this light, splicing of the cdt transcripts could serve as an avenue for posttranscriptional control, regulating the expression of Cdt proteins.…”
Section: Discussionmentioning
confidence: 99%